Percutaneous mechanical thrombectomy in a real‐world pulmonary embolism population: Interim results of the FLASH registry. Issue 4 (3rd February 2022) - Toma, Catalin; Bunte, Matthew C.; Cho, Kenneth H.; Jaber, Wissam A.; Chambers, Jeffrey; Stegman, Brian; Gondi, Sreedevi; Leung, Daniel A.; Savin, Michael; Khandhar, Sameer; Kado, Herman; Koenig, Gerald; et al.
Abstract: Objectives: The FlowTriever All‐Comer Registry for Patient Safety and Hemodynamics (FLASH) is a prospective multi‐center registry evaluating the safety and effectiveness of percutaneous mechanical thrombectomy for treatment of pulmonary embolism (PE) in a real‐world patient population (NCT03761173). This interim analysis reports outcomes for the first 250 patients enrolled in FLASH. Background: High‐ and intermediate‐risk PEs are characterized by high mortality rates, frequent readmissions, and long‐term sequelae. Mechanical thrombectomy is emerging as a front‐line therapy for PE that enables immediate thrombus reduction while avoiding the bleeding risks inherent with thrombolytics. Methods: The primary endpoint is a composite of major adverse events (MAE) including device‐related death, major bleeding, and intraprocedural device‐ or procedure‐related adverse events at 48 h. Secondary endpoints include on‐table changes in hemodynamics and longer‐term measures including dyspnea, heart rate, and cardiac function. Results: Patients were predominantly intermediate‐risk per ESC guidelines (6.8% high‐risk, 93.2% intermediate‐risk). There were three MAEs (1.2%), all of which were major bleeds that resolved without sequelae, with no device‐related injuries, clinical deteriorations, or deaths at 48 h. All‐cause mortality was 0.4% at 30 days, with a single death that was unrelated to PE. Significant on‐table improvements in hemodynamics were noted, including an average reduction in mean pulmonary artery pressure of 7.1 mmHg (22.2%, p  < 0.001). Patient symptoms and cardiac function improved through follow‐up. Conclusions: These interim results provide preliminary evidence of excellent safety in a real‐world PE population. Reported outcomes suggest that mechanical thrombectomy can result in immediate hemodynamic improvements, symptom reduction, and cardiac function recovery.